AB0760 DRUG SURVIVAL AND EFFICACY OF USTEKINUMAB AND SECUKINUMAB IN PSORIATIC ARTHRITIS: A REAL-WORLD MULTICENTRIC COHORT OF 186 PATIENTS. (June 2019) - Letarouilly, Jean-Guillaume; Sellam, Jeremie; Richette, Pascal; Dieudé, Philippe; Claudepierre, Pascal; Richard, Corinne Miceli; Houvenagel, Eric; Nguyen, Chi Duc; Guyot, Marie-Hélène; Segaud, Nicolas; Marguerie, Laurent; Deprez, Xavier; et al.
Abstract : Background: Ustekinumab (UST) and secukinumab (SEK) are new Biologic Disease-modifying antiRheumatic Drugs (bDMARDs) available in psoriatic arthritis (PsA), targeting respectively IL12-23 and IL 17. Real-world data are missing for these drugs, despite the wide use. There is only one previous published study including 160 patients (1) receiving UST, but not SEK. Objectives: To evaluate the characteristics of the patients with PsA treated by UST or SEK and to assess real life drug survival and efficacy of UST and SEK in PsA. Methods: This is a national, retrospective, multicentric study from patients suffering from PsA (CASPAR criteria) from July 2011 to april 2018. Drug survival was defined as the time from initiation to discontinuation (stop/switch) of bDMARDs. Kaplan-Meier survival curves and Cox-regression analyses [hazard ratios (HR) and 95% confidence intervals (CIs)] were used adjusting for patient demographics, disease characteristics, co-therapy with methotrexate, and line of treatment with ustekinumab. For peripheral involvement, treatment was considered to be effective for patients with a combined favorable expert opinion and/or > 30% clinical improvement of swollen and tender joint counts. For axial involvement, efficacy criteria were: improvement of BASDAI by at least 2 points on a scale from 0 to 10 or 50% improvement and/or expert opinion. Results: 186 patients were included with a mean follow-up ≥ 6 months: 111 patients under UST and 75 under SEK. The mean age was 51.5 (12.9) years old, 55% of patients were women and the body mass index was 27.3 (5.8) kg/m². The disease duration was 10.8 (8.1) years. Patients were bDMARDs-naïve in 15%. The median drug survivals for UST and SEK were respectively 12 and 14 months (Fig1 ). A propensity score cannot be used to compare the two bDMARDs, since the number of patients was too small. Smoking was associated with an unfavourable drug survival for SEK (HR= 0.22, 95%CI 0.91), whereas CRP levels were associated with a favorable one for UST (HR=1.009, 95%CI 1.003–1.016). Nine patients under SEK and 2 under UST stopped their treatments due to side effects. Conclusion: This is the first real-world study for drug survival on PsA for SEK and one with the largest number of patients for UST. Drug survival of UST and SEK seems similar to TNF inhibitors' (2). References: [1] Iannone F, et al. Drug survival and effectiveness of ustekinumab in patients with psoriatic arthritis. Real-life data from the biologic apulian registry (BIOPURE). Clin Rheumatol. 2018;37:667–75. [2] Walsh JA, et al. Care Spec Pharm. 2018;24:623-631 Disclosure of interests: Jean-Guillaume Letarouilly: None declared, Jeremie Sellam: None declared, Pascal Richette Consultant for: Grunenthal, Horizon, Speakers bureau: astraZeneca, Grunenthal, Philippe Dieudé: None declared, Pascal Claudepierre Consultant for: Honoraria from Novartis as steering committe of this survey, Corinne Miceli Richard Grant/research support from: MSD, Pfizer, abbVie, Biogen, UCB, Novartis, Consultant for: abbvie, Novartis, BMS, Eric Houvenagel Speakers bureau: Lilly, Novartis, Janssen, Chi Duc Nguyen: None declared, Marie-Hélène Guyot: None declared, Nicolas Segaud: None declared, Laurent Marguerie: None declared, Xavier Deprez Speakers bureau: Novartis Janssen, Jean-Hugues Salmon Speakers bureau: Janssen Novartis, Guy Baudens Grant/research support from: Financial Grant from NordicPharma, Consultant for: Roche SAS, Maeva Kyheng: None declared, Julien Paccou Speakers bureau: Novartis Janssen, Elisabeth Gervais Grant/research support from: Roche, Pfizer, Consultant for: Bristol-Myers Squibb, UCB, René-Marc Flipo Consultant for: Honoraria from Novartis as steering committe of this survey